2011
DOI: 10.1007/s10482-011-9661-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of culturable endophytic actinobacteria associated with Artemisia annua L.

Abstract: Endophytic actinobacteria isolated from Artemisia annua were characterized and evaluated for their bioactivities. A total of 228 isolates representing at least 19 different genera of actinobacteria were obtained and several of them seemed to be novel taxa. An evaluation of antimicrobial activity showed that more isolates possessed activity towards plant pathogens than activity against other pathogenic bacteria or yeasts. High frequencies of PCR amplification were obtained for type I polyketide synthases (PKS-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 49 publications
8
58
3
Order By: Relevance
“…Compared to earlier studies using the same primers (Gao & Huang, 2009;Li et al, 2012), the percentages of Streptomyces strains carrying type I PKS and type II PKS genes were similar whereas for NRPS and FADH 2 -dependent halogenase genes the proportion of positive strains was smaller in our study, either because the strains lacked the genes or the primers were unsuitable for the amplification of those genes.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Compared to earlier studies using the same primers (Gao & Huang, 2009;Li et al, 2012), the percentages of Streptomyces strains carrying type I PKS and type II PKS genes were similar whereas for NRPS and FADH 2 -dependent halogenase genes the proportion of positive strains was smaller in our study, either because the strains lacked the genes or the primers were unsuitable for the amplification of those genes.…”
Section: Discussioncontrasting
confidence: 83%
“…growing in Tarim to analyse their diversity and antimicrobial potential. As in previous studies on other plant species (Kim et al, 2012b;Li et al, 2012), most of the actinobacterial strains isolated from the liquorice species belonged to the genus Streptomyces. The composition of the antimicrobials produced by G. glabra differs from those produced by G. inflate (Kondo et al, 2007;Xie et al, 2010), plausibly influencing the different species compositions of the G. glabra and G. inflate associated culturable actinobacteria communities.…”
Section: Discussionsupporting
confidence: 69%
“…collected from 113 plants and they were categorized on the basis of 16S rRNA gene sequences into six families; Streptosporangiaceae (40%), Streptomycetaceae (27%), Thermomonosporaceae (16%), Micromonosporaceae (8%), Pseudonocardiaceae (8%) and Actinosynnemataceae (2%). 11 Notably, the genus Streptomyces in the family Streptomycetaceae accounted for only 26%, meaning that rare actinomycetes (non-Streptomyces) make up 74% of the total and other reports also indicated that rare actinomycetes are majority in plant, [12][13][14] although Kaewkla and Franco reported that Streptomyces strains accounted for 72% of endophytic actinomycetes isolated from Australian native trees. 15 It remains to be seen whether this promising new source of bioactive materials will bear fruit, but the signs are promising.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the presence of genes coding for polyketide synthase (PKS) or nonribosomal peptide synthetase (NRPS) have been frequently carried out and a few reports found, as an indicator, that 21-66%, 45-82% and 33-100% of endophytic actinomycetes have type I PKS (PKS-I), type II PKS (PKS-II) and NRPS, respectively. 11,12,14 It is widely believed that the potential of secondary metabolites with biological activities from endophytic actinomycetes is just as great as that achieved from soil actinomycetes. [16][17][18][19][20] As results of our exploration, we have already found several novel compounds from endophytic actinomycetes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the isolates obtained, Micromonospora sp. have previously been identified as endophyte from roots of medicinal plants such as Ainsliaea henryi and Stellera chamaejasme L., (Zhao et al 2011) roots of Artemisia annua (Li et al 2012b), leaves of Maytenus austroyunnanensis (Qin et al 2009) and roots of Triticum aestivum L. (Coombs and Franco 2003). Endophytic Brevibacterium halotolerans with growth promoting activities was previously known from the roots of the halophyte, Prosopis strombulifera (Sgroy et al 2009).…”
Section: Resultsmentioning
confidence: 99%